Plasmodium falciparum rhoptry neck protein 5 peptides bind to human red blood cells and inhibit parasite invasion (2014)
Plasmodium falciparum malaria parasite invasion of erythrocytes is an essential step in host infection and the proteins involved in such invasion are the main target in developing an antimalarial vaccine. Secretory organelle-derived proteins (micronemal AMA1 protein and the RON2, 4, and 5 rhoptry neck proteins) have been recently described as components of moving junction complex formation allowing merozoites to move into a newly created parasitophorous vacuole. This study led to identifying RON5 regions involved in binding to human erythrocytes by using a highly robust, sensitive and specific receptor-ligand interaction assay; it is further shown that the RON5 protein remains highly conserved throughout different parasite strains. It is shown that the binding peptide-erythrocyte interaction is saturable and sensitive to chymotrypsin and trypsin. Invasion inhibition assays using erythrocyte binding peptides showed that the RON5-erythrocyte interaction could be critical for merozoite invasion of erythrocytes. This work provides evidence (for the first time) suggesting a fundamental role for RON5 in erythrocyte invasion. © 2013 Elsevier Inc.